2019
DOI: 10.1063/1.5138191
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic resistance measurement in a YBCO wire under perpendicular magnetic field at various operating temperatures

Abstract: Dynamic resistance plays an important role in certain high-Tc superconducting (HTS) applications where an HTS coated conductor carries a DC current exposed to an AC magnetic field. Here, we report measurements of the dynamic resistance in a 4 mm-wide YBCO coated conductor under a perpendicular AC magnetic field at 77 K, 70 K, and 65 K. Dynamic resistance was measured at three different frequencies for the reduced current, i (It/Ic0), ranging from 0.04 to 0.9, where It is the DC current level and Ic0 is the sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 29 publications
7
31
0
Order By: Relevance
“…when i = 0, from view A, it clearly shows only shielding currents are induced at the edges, as highlighted in black circles where magnetization loss is generated. No current flows in the central region, which is consistent to previous papers [14], [15], [16], [17], [18]. When i = 0.5 and B a = 5 mT, there is no dynamic resistance as shown in Fig.…”
Section: Figure 10 Dynamic Resistance Comparison Between the Inner La...supporting
confidence: 91%
See 1 more Smart Citation
“…when i = 0, from view A, it clearly shows only shielding currents are induced at the edges, as highlighted in black circles where magnetization loss is generated. No current flows in the central region, which is consistent to previous papers [14], [15], [16], [17], [18]. When i = 0.5 and B a = 5 mT, there is no dynamic resistance as shown in Fig.…”
Section: Figure 10 Dynamic Resistance Comparison Between the Inner La...supporting
confidence: 91%
“…To date, many previous works on dynamic resistance and total loss have mainly focused on single HTS coated conductor tapes [12], [13], [14], [15], [16], [17] or stacks [3], [18], [19], [20], [21], [22], [23]. In terms of the operating conditions, the dependence of dynamic resistance and total loss of single REBCO coated conductors on magnetic field/DC current/temperature/frequency have been investigated through experiments [13], [14], [15]. Dynamic resistance and total loss of a three-tape HTS stack have been measured where both magnetization loss and dynamic loss in the stack were smaller than a single tape due to the shielding effect [18].…”
Section: Introductionmentioning
confidence: 99%
“…[7] YBa 2 Cu 3 O 7Àδ (YBCO) is one of the most interesting superconductors as its upper critical magnetic field and critical current density are quite large among HTSC; this compound is more exploited for intense magnetic field production, power cables transmission. [8] For these reasons, many recent works focus on YBCO's properties improvement [9] and properties investigation, such as critical temperature prediction, [10] temperature resistivity, transition region broadening, magnetic penetration depth, and coherence length. Recently, several groups had studied the scaling behavior for various samples of YBCO grown under different conditions.…”
mentioning
confidence: 99%
“…Recently, several groups had studied the scaling behavior for various samples of YBCO grown under different conditions. [8,[11][12][13][14][15][16][17] Slimani et al investigated the flux pinning properties of YBCO added by WO 3 nanoparticles. [18] Also, the impact of Dy 2 O 3 nanoparticles addition on the properties of porous YBCO ceramics is analyzed by Almessiere et al [19] In this investigation, on the one hand, the magnetization measurements have been performed on high-temperature superconductor's single-crystal YBa 2 Cu 3 O 7Àδ at large ranges of temperature T (15À85 K) and in magnetic fields up to 6 T. The temperature dependence of the magnetic penetration depth is estimated from the slope of the linear M(lnH) dependence in the London regime for three directions of the applied magnetic field with the c-axis (θ ¼ 0 , 30 , and 45 ), θ is the angle between the direction of the applied magnetic field and the crystallographic c-axis.…”
mentioning
confidence: 99%
“…The dynamic loss is calculated by measuring the voltage along with the transport current of the coated conductor sample. The measurement method has been extensively applied to much experimental exploration of dynamic loss and dynamic resistance of HTS CCs [16,63,64,[158][159][160][161]. Ogawa has studied the magnetization loss and dynamic loss of an HTS pancake coil with a double pick-up coil method and found that the dynamic resistance can mitigate the DC of the coil when it is operated in the permanent current mode [135].…”
Section: Electric Methodsmentioning
confidence: 99%